Material Characterization of High Dielectric Constant Polymer–Ceramic Composite for Embedded Capacitor to RF Application - Yang Rao; Jireh Yue; C. P. Wong (Active and Passive Electronic Components)
Embedded capacitor technology can improve electrical performance and reduce assembly cost compared with traditional discrete capacitor technology. Polymer–ceramic composites have been of great interest as embedded capacitor material because they combine the processability of polymers with the desired electrical properties of ceramics. A novel nano-structure polymer–ceramic composite with very high dielectric constant (εr∼150 , a new record for the highest reported εr value of nano-composite) has been developed in our previous work. RF application of embedded capacitors requires that insulating material have high dielectric constant at high frequency (GHz), low leakage current, high breakdown voltage and high reliability. A set of electrical tests have been conducted in this work to characterize the properties of the in house developed novel high dielectric constant polymer–ceramic nano-composite. Results show that this material has faily high dielectric constant in the RF range, low electrical leakage and high breakdown voltage. 85/85 TH aging test has been performed and it had shown this novel high K material has good reliability. An embedded capacitor prototype with capacitance density of 35 nF/cm2 has been manufactured using this nano-composite with spinning coating technology. This novel nano-composite can be used for the integral capacitors in the RF applications.